Il corpo desiderato: differenze di genere - Fobert Veutro, Maria (SocietàMutamentoPolitica, 2021)
This work presents a survey on gender identity – conducted on a sample of about 4,000 Italians – which explores the differences between genders regarding embodiment, that is the consciousness we have of our body, the awareness of “having” a body and “being” a body, and the relationship between these differences, age, and political orientation. The debate nature vs. nurture, that is whether the differences between genders are more related to genetic heritage or to the influence of the environment, is millennia old and it is outlined with mentions from ancient Greece to the French Revolution and positivism, also to the different waves of feminism, and finally to the contemporary contributions of neuroscientists. In order to study empirically, on a large number of cases, the influence of gender on conceptions and desires about one’s own body, trying to circumvent “social desirability”, an original tool was used. This tool consists of a battery of twenty-eight self-anchoring scales which, unusually for a survey, explore the desire to possess bodily faculties peculiar to animals and plants, or to natural events, which human beings do not possess or which they possess in a reduced form. Therefore, no direct questions are asked about value options or attitudes; nor are social meanings offered, as “non-social” objects are asked to be evaluated. The choices of the subjects and the relationships with the mentioned properties (age and political orientation) are analyzed and interpreted.